Deformation kinetics of nanocrystalline nickel - Li, Yujiao; Müller, Johannes; Höppel, Heinz Werner; Göken, Mathias; Blum, Wolfgang (Acta Materialia, 2007)
The work hardening and the strain rate sensitivity of flow stress were studied in the temperature range from 298 to 473 K for nanocrystalline (NC) nickel with average grain sizes of about 25 and 80 nm produced by pulsed electrodeposition. The rate of work hardening, the maximum flow stress and the strain rate sensitivity of flow stress increase with decreasing grain size. The data are compared to published data for NC Ni and found to be consistent. The common analysis of strain rate sensitivity in terms of thermal activation is critically discussed. It is proposed that the activation analysis gives information about thermally activated processes at grain boundaries which may be related with recovery of dislocations.
Created from Fastlane, Scopus look-up
Keywords: Activation volume; Grain boundaries; Nanocrystalline Ni; Strain rate sensitivity; Work hardening